Test-Retest Reliability and Internal Consistency of a Nigerian (Yoruba) Version of Disabilities of The Arm, Shoulder and Hand Questionnaire (DASH -Y) (African Journal of Biomedical Research, 2020)
The disabilities of the arm, shoulder and hand (DASH) questionnaire is a self-administered region-specific outcome instrument developed to measure upper extremity disability and symptoms. It is a widely used instrument that has been recently translated into Yoruba (a major indigenous language in Nigeria, DASH-Y). The aim of this study was to assess the test-retest reliability and internal consistency of the Yoruba version of DASH questionnaire in order to further enhance its use in Yoruba-speaking populations. Fifty-two patients with upper extremity musculoskeletal disorders, recruited purposively participated in this cross-sectional survey. They comprised of 28 (53.8%) males and 24 (46.2%) females who were able to read and write in both English and Yoruba Languages. Participants completed the Yoruba versions of DASH on two occasions. Internal consistency was evaluated with Cronbach’s alpha. Test-retest reliability was analyzed by intraclass coefficient (ICC). Alpha was set at 0.05. Participants’ were aged 43.33 years ±12.59 years. Test retest reliability of the DASH-Y was excellent (ICC= 0.959, p=0.001).  The Cronbach’s alpha co-efficient was high (α ranged from 0.894-0.901) for the entire items on the scale.  The Yoruba version of DASH questionnaire is a reliable outcome measure for individuals with upper extremity musculoskeletal disability. It can be used for assessing effectiveness of therapeutic interventions in the Yoruba speaking populations.